Interactions of Perisbivalvin, Apioside, and Pelargonidine 3-Sambubioside Against PTGS2 Receptors - Ketut Agus Adrianta; Puguh Santoso; Putu Windra Gunawan; Dewa Ayu Ika Pramitha (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
Inflammation is a normal protective response to tissue injury that involves various physiological processes in the body. Perisbivalvin, apioside, and pelargonidine 3-sambubioside are anthocyanin compounds found in magenta plants. The purpose of this study was to obtain a candidate for a new compound as an anti-inflammatory agent targeting the PTGS2 receptor before in vivo testing. Molecular docking in silico with PDB code 5IKR was carried out by optimizing 2 and 3-dimensional chemical structures, method validation, and docking between perisbivalvin compounds and the comparison compound mefenamic acid. The results obtained were docking perisbivalvin -7.63 kcal/mol, apioside -0.77 kcal/mol, and pelargonidine -5.74 kcal/mol, while the bond energy of the comparison compound was -7.52 kcal/mol through hydrogen bonding with amino acids TYR 385A and SER 530A. The prediction results of the test compounds and comparison compounds were classified as class 4 toxicities. Perisbivalvin compounds have anti-inflammatory potential because they can bind to the PTGS2 protein.